A novel contour-based registration of lateral cephalogram and profile photograph. (January 2018) - Wang, Shumeng; Li, Huiqi; Zou, Bingshuang; Zhang, Wanjun
Highlights: A new contour-based registration method is proposed to register lateral cephalograms to profile photographs. A hierarchical contour detection algorithm is employed to obtain contours of forehead and nose in lateral cephalograms and profile photographs. A new curve based coarse-to-fine strategy is used to align the contour pairs and identically estimate the transformation. Comparative experiments show that the proposed method achieves higher performance in registration accuracy and robustness. Abstract: A contour-based automatic registration method of lateral cephalograms and profile photographs is proposed to facilitate the accurate measurement of anteroposterior (AP) position of maxillary central incisors relative to the forehead. There are mainly three steps in the proposed method. First, a hierarchical contour detection algorithm is employed to obtain contours of forehead and nose in lateral cephalograms and profile photographs, respectively. Curve deviation around Nasion of Soft Tissue (Ns) is further corrected using an iterative polynomial curve fitting algorithm according to the characteristics of cephalograms. Second, the coarse registration is performed based on four landmark pairs using a routine least squares method for each image pair, and then the contours are roughly matched. Finally, the coarse registration is further refined by applying the coherent point drift (CPD) algorithm to all the contour points. Using image pairs of lateral cephalograms and profile photographs from 49 Chinese patients, we show that the proposed method achieves higher performance in terms of accuracy and robustness than the existing methods.